Réponses

Meilleure réponse !
  • Omnes
  • Modérateur confirmé
2014-02-28T23:56:27+01:00
Salut,

A = (2x - 1)² - (3x + 2) (2x - 1)
A = (4x² - 4x + 1) - (6x² - 3x + 4x -2)
A = 4x² - 4x + 1 - 6x² -x + 2
A = -2x² -5x + 3

A = (2x - 1)² - (3x + 2) (2x - 1)
A = (2x-1)(2x-1) - (3x+2)(2x-1)
A = (2x-1)[(2x-1) - (3x+2)]
A = (2x-1)(2x-1-3x-2)
A = (2x-1)(-x-3)

Pour x = √3
A = (2 *√3 -1)(-√3-3)
A = (2*√3)*(-√3) -3*(2√3) + 1√3 + 3
A = -2√3² - 6√3 + 1√3 + 3
A = -2*3 - 5√3 + 3
A = -6 -5√3 +3
A = -3 - 5√3


Bonne soirée !